2019
DOI: 10.1186/s12870-019-2065-7
|View full text |Cite|
|
Sign up to set email alerts
|

Functional analysis of GhCHS, GhANR and GhLAR in colored fiber formation of Gossypium hirsutum L

Abstract: BackgroundThe formation of natural colored fibers mainly results from the accumulation of different anthocyanidins and their derivatives in the fibers of Gossypium hirsutum L. Chalcone synthase (CHS) is the first committed enzyme of flavonoid biosynthesis, and anthocyanidins are transported into fiber cells after biosynthesis mainly by Anthocyanidin reductase (ANR) and Leucoanthocyanidin reductase (LAR) to present diverse colors with distinct stability. The biochemical and molecular mechanism of pigment format… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…In addition, the 4Cl family included positively selected genes. In this pathway, chalcone synthase (CHS) plays a core role in naringenin chalcone biosynthesis by condensing 4‐coumaroyl‐CoA, produced via the phenylpropanoid pathway (Gao et al, 2019; Figure 5a). Interestingly, we found that the CHS gene family was expanded and contained 11 copies in Cp, the number of which was higher than the four copies identified in Ca and the one copy in At (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the 4Cl family included positively selected genes. In this pathway, chalcone synthase (CHS) plays a core role in naringenin chalcone biosynthesis by condensing 4‐coumaroyl‐CoA, produced via the phenylpropanoid pathway (Gao et al, 2019; Figure 5a). Interestingly, we found that the CHS gene family was expanded and contained 11 copies in Cp, the number of which was higher than the four copies identified in Ca and the one copy in At (Figure 5b).…”
Section: Resultsmentioning
confidence: 99%
“…LAR channels leucoanthocyanidins into the proanthocyanidin biosynthesis, which is in competition with the anthocyanidin formation catalysed by ANS. There is also a competition between 3-glucosyltransferase (3GT) and ANR for anthocyanidins [ 59 ]. While 3GT generates stable anthocyanins through the addition of a sugar group to anthocyanidins, ANR channels anthocyanidins into the proanthocyanidin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have shown that PAs are the main component of pigment deposition in BCF ( Li et al, 2013 ; Feng et al, 2014 ; Xiao et al, 2014 ; Yan et al, 2018 ), and their content reaches typically peaks at 30 DPA ( Feng et al, 2014 ). The biosynthesis of proanthocyanidins precursors regulates the FB pathway to mediate the gene expression of flavonoid metabolism pathway for the development of BCF ( Hua et al, 2007 ; Xiao et al, 2007 , 2014 ; Feng et al, 2013 ; Li et al, 2013 ; Tan et al, 2013 ; Gao et al, 2019 ). Earlier research demonstrated that the synthesis of proanthocyanidins in fiber is the main reason for the shortened elongation period, thus halting the early elongation of BCF ( Qiu, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthocyanidin reductase ( ANR ) is a key structural gene in the PA pathway ( Feng et al, 2014 ). Recently, these two genes, LAR and ANR , have been verified for their transgene functionality, enabling that the development of new colored cotton germplasm has been developed ( Gao et al, 2019 ). In the last decade, transcriptomic or proteomic analyses were used to uncover the PA precursor synthesis pathway involved in fiber pigmentation.…”
Section: Introductionmentioning
confidence: 99%